Learning Arabic Reading Skills Based on E-Learning Using SIKULI during the Covid-19 Pandemic - Budi Santoso Wibowo; Widiya Yul; Riko Andrian (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2021)
Abstract This paper explores the steps for learning Arabic reading skills based on e-Learning using SIKULI and the advantages and disadvantages of e-Learning. The approach is a descriptive qualitative approach with three data collection techniques, namely: (1) observation, (2) interviews, and (3) documentation. The results showed that there were three steps taken by lecturers in implementing e-Learning-based Arabic reading skills using SIKULI, namely: (1) pre-learning, (2) implementation of learning, and (3) evaluation of learning. Researchers also found several advantages of implementing e-Learning-based Arabic reading skills using SIKULI, namely: (1) assisting the internal quality assurance system (SPMI) through monitoring and evaluation, (2) practical and flexible, (3) providing supporting features and menus. However, besides having various advantages, as an e-Learning that has just been built and used, SIKULI is also not free from multiple shortcomings, namely: (1) frequently interrupted system, (2) no notifications, (3) poor internet network. Nevertheless, The results of this sytudy are hoped to provide insight and alternative solutions for lecturers in carrying out online learning of Arabic reading skills during the Covid-19 pandemic. Keywords: Learning, Arabic Reading Skills, e-Learning, SIKULI, Covid-19